The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/conphys/coab096
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cortisol and corticosterone concentrations in humpback whale (Megaptera novaeangliae) baleen are associated with different causes of death

Abstract: Baleen whales are subject to a myriad of natural and anthropogenic stressors, but understanding how these stressors affect physiology is difficult. Measurement of adrenal glucocorticoid (GC) hormones involved in the vertebrate stress response (cortisol and corticosterone) in baleen could help fill this data gap. Baleen analysis is a powerful tool, allowing for a retrospective re-creation of multiple years of GC hormone concentrations at approximately a monthly resolution. We hypothesized that whales that died … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…abundance [19] and body size [20], modern populations continue to face threats from fisheries entanglement [21], climate-change-induced shifts in prey distribution and abundance [22], noise pollution [23], ship strikes [24], marine debris [25], and, in some areas, continued commercial whaling [26].…”
Section: Highlightsmentioning
confidence: 99%
“…abundance [19] and body size [20], modern populations continue to face threats from fisheries entanglement [21], climate-change-induced shifts in prey distribution and abundance [22], noise pollution [23], ship strikes [24], marine debris [25], and, in some areas, continued commercial whaling [26].…”
Section: Highlightsmentioning
confidence: 99%
“…Furthermore, the necropsy report indicated that the cause of death was probable blunt trauma from a vessel strike. An acute cause of death (e.g., vessel strike) reduces the possibility of other factors (e.g., chronic stress, starvation, or a change in habitat use following injury or entanglement in fishing gear) causing long-term changes in body chemistry that can be reflected on a baleen plate. ,, …”
Section: Resultsmentioning
confidence: 99%
“…As the baleen grows from the gum tissue (i.e., the Zwischensubstanz), it continually erodes on the lingual side, creating a dense fringe mat, which acts as the filter. As the plates grow dorsoventrally, at an average of ∼20 cm/year (range of 12–32 cm/year), the chemical signature acquired when the baleen first emerged is preserved, as in human hair. This makes baleen a useful tissue for investigating key physiological and phenological variables over time, including individual movements and diet patterns via stable isotopes, hormonal changes related to breeding and feeding, and variation in exposure to trace metal pollution . However, only a limited time window for analysis is available (the most recent 3–13 years) as the plate eventually erodes distally and is replaced by new keratinous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…For research collaborators, this has inspired studies that would not have been possible without the large collective investment in building a platform and populating it with a comprehensive and contemporary dataset 48,49 . To date the NPPID collaboration has contributed data to seven other peer reviewed papers 17,26,27,[50][51][52][53] . Accessible information about North Paci c humpback whale individuals has also proven very useful for resource managers, for example tracking shing gear entanglement cases and individual identi cation and past sighting histories of dead or stranded whales 54 .…”
Section: Accessibility and User Agreementsmentioning
confidence: 99%